Sleep and Pain in Veterans with Chronic Pain: Effects of Psychological Pain Treatment and Temporal Associations - Wilson M; Skeiky L; Muck RA; Miller MA; Hansen DA; Williams RM; Jensen MP; Van Dongen HPA (Nature and Science of Sleep, 2023)
Marian Wilson,1,2,* Lillian Skeiky,2,3,* Rachael A Muck,2,3 Megan A Miller,4 Devon A Hansen,2,3 Rhonda M Williams,4,5 Mark P Jensen,5 Hans PA Van Dongen2,3 1College of Nursing, Washington State University, Spokane, WA, USA; 2Sleep and Performance Research Center, Washington State University, Spokane, WA, USA; 3Department of Translational Medicine and Physiology, Washington State University, Spokane, WA, USA; 4Rehabilitation Care Service, VA Puget Sound Health Care System, Seattle, WA, USA; 5Department of Rehabilitation Medicine, University of Washington, Seattle, WA, USA*These authors contributed equally to this workCorrespondence: Marian Wilson, College of Nursing, Washington State University, 103 E. Spokane Falls Blvd, Spokane, WA, 99202, USA, Tel +1 509 324 7443, Email marian.wilson@wsu.eduIntroduction: Chronic pain is highly prevalent in US military Veterans. Non-opioid and non-pharmacologic treatments are recommended when clinically appropriate, but research on the mechanisms underlying benefits of these treatments is lacking. Here, we examined the role of sleep in the effects of three non-pharmacologic pain treatments in Veterans. Specifically, we investigated whether treatment effects on sleep predicted treatment effects on pain occurring later, or vice versa.Methods: Veterans enrolled in a randomized controlled trial were invited to participate in this supplementary sleep study. A total of 174 Veterans were randomized to one of three 8-session, in-person, group-based pain treatments: hypnosis, mindfulness meditation, or education control. Measurements included self-reported sleep disturbance, pain intensity, and pain catastrophizing; sleep duration was assessed with actigraphy. Sleep and pain measurements were obtained at baseline, posttreatment, and 3-month posttreatment follow-up.Results: At baseline, average pain intensity was moderate (mean ± SD: 5.7 ± 1.7 on the 0– 10 Numeric Rating Scale), pain catastrophizing was just below the clinically relevant threshold (mean ± SD: 28.6 ± 12.2 on the Pain Catastrophizing Scale), and subjective sleep disturbance exceeded the US population average (mean ± SD: 58.5 ± 8.1 on the Patient Reported Outcomes Measurement Information System Sleep Disturbance – Short Form). By contrast, objective sleep duration was consistent with the recommended daily sleep amount of 7– 8 h for adults (mean ± SD: 8.3 ± 1.4 h). Across treatment conditions, pain intensity, pain catastrophizing, and subjective sleep disturbance were significantly less at posttreatment and 3-month follow-up than at baseline (p < 0.001). Actigraphic sleep duration did not differ significantly as a function of time. There was a high degree of covariation among the measures of pain intensity, pain catastrophizing, and sleep disturbance (p < 0.05). However, self-reported sleep disturbance was not significantly correlated with actigraphic sleep duration (|r| 0.05). Sleep and pain variables observed at prior assessments predicted these same variables at subsequent assessments. There was no significant evidence that changes in pain preceded changes in sleep or that changes in sleep preceded changes in pain (all p > 0.05).Discussion: For this study’s Veterans, treatment-related changes in sleep and pain appeared to occur in parallel. The concomitant changes in sleep and pain suggest that therapies improving pain in Veterans may yield attendant benefits for the treatment of sleep, and possibly vice versa.Keywords: chronic pain, complementary and integrative treatments, sleep, Veterans